Werner Reutter: A Visionary Pioneer in Molecular Glycobiology. (16th June 2017) - Hinderlich, Stephan; Tauber, Rudolf; Bertozzi, Carolyn R.; Hackenberger, Christian P. R.
Abstract : A creative pioneer : Werner Reutter (1937–2016) was a scientist who both made fundamental discoveries in glycobiology and reached out to disciplines beyond his core field. Many of his former colleagues and students will remember his desire to exchange research ideas, which ultimately contributed to the birth of new research fields.